Sensibilidade celular e de biofilme de Enterococcus sp. aos desinfetantes de uso industrial - Mücke, Naieli (2016)
The Enterococcus sp. may be isolated from humans, animals and environment. It presents high tolerance to extreme factors such as pH, temperature and salt concentration. It has an important role as a starter culture in different products such yogurts and cheeses, and as producers of enterocinas. However, its potential as agents of serious infections has increasing, especially because can acquire high resistance to antimicrobials and biocides. The food industry equipment’s are willing to high microbiological contamination due to the presence of substrates for microorganisms. When dirty, allow the microorganisms grow and biofilm formation, contaminating the final product. The aim of this work was isolated the genus Enterococci strains of equipment’s on pork cooked sausages and yogurts lines, identified through molecular techniques and check the biocide susceptibility of seven formulations of different industrial disinfectants and the action of these on the biofilm. On the yogurts line samples analyzed there was no grow of indicative colonies. Of the 36 samples analyzed in the sausage line, 40 colonies were selected to undergo genotypic evaluation, showing that 70.0% (28 isolates) had the tuf gene that identifies the genus Enterococcus sp. It was verified that 7.1% belonged to the genus E. faecium, 7.1% E. gallinarum, 7.1% E. casseliflavus/E. flavencens and 78.7% of the isolates were not identified to species level using the oligonucleotides used in this study. In assessing the sanitizing action on cells of Enterococcus sp. in the presence of water there was no product that could be used effectively on grow control of enterococci. In tests using BHI and sanitizing the isolates were less developed in the presence of quaternary ammonia sanitizer D at all times, and in the time 15 minutes, 1, 2, 3 and 24 hours there was no development. Further development occurred in the presence of chlorine dioxide, sodium hypochlorite and peracetic acid at all times, and for the first two products all isolates were resistant at all times. Regardless of the sanitizers and biofilm formed, no chemical agent was effective in complete elimination of Enterococcus cells. Note that biofilms were formed even on the sanitized surfaces even though the average concentration-time recommended by the manufacturer was used. Indispensable to emphasize that the results confirm the importance of preventive actions in the industries to avoid the resistance of microorganisms to certain compounds and maximize the efficiency of applied hygiene procedures.